Kinematic analysis of 24-hour recording of walking pattern in patients with vascular parkinsonism. (3rd October 2015) - Terashi, Hiroo; Utsumi, Hiroya; Ishimura, Yohei; Aizawa, Hitoshi; Yoneyama, Mitsuru; Mitoma, Hiroshi
Abstract : Background : There is a need to define the basic characteristics of various kinematic parameters recorded during walking in patients with vascular parkinsonism (VP). The present study was designed to determine the kinematic features of walking in VP patients. For this purpose, gait acceleration and gait cycle were recorded continuously over 24-h period of daily living in VP patients, patients with Parkinson's disease (PD), and healthy subjects. Methods : We used our newly developed 24-h monitoring device, the portable gait rhythmogram, which records gait during walking, and computes gait-induced accelerations with pattern matching algorithm. We studied nine VP patients with history of multiple lacunar infarcts (mean age ± standard deviation (SD): 72.6 ± 5.0 years, 7 men), 39 PD patients (mean age ± SD: 70.8 ± 5.8 years, 18 women), and 15 normal control subjects (mean age ± SD: 67.9 ± 4.7 years, 9 men). Results : The "amount of overall movements per 24 h" was lower in VP and PD, compared with the control, with no significant differences between the two groups. Gait acceleration during walking was significantly lower ( p < 0.01 in each case), while the gait cycle was the same in VP and PD patients compared with the control. Conclusions : The results suggest that deficit in force production and preservation of gait rhythm are common features of walking patterns in VP and PD patients.